Generation and Characterization of Smac/DIABLO-Deficient Mice - Okada, Hitoshi (American Society for Microbiology, 2002)
The mitochondrial proapoptotic protein Smac/DIABLO has recently been shown to potentiate apoptosis by counteracting the antiapoptotic function of the inhibitor of apoptosis proteins (IAPs). In response to apoptotic stimuli, Smac is released into the cytosol and promotes caspase activation by binding to IAPs, thereby blocking their function. These observations have suggested that Smac is a new regulator of apoptosis. To better understand the physiological function of Smac in normal cells, we generated Smac-deficient (Smac(−/−)) mice by using homologous recombination in embryonic stem (ES) cells. Smac(−/−) mice were viable, grew, and matured normally and did not show any histological abnormalities. Although the cleavage in vitro of procaspase-3 was inhibited in lysates of Smac(−/−) cells, all types of cultured Smac(−/−) cells tested responded normally to all apoptotic stimuli applied. There were also no detectable differences in Fas-mediated apoptosis in the liver in vivo. Our data strongly suggest the existence of a redundant molecule or molecules capable of compensating for a loss of Smac function.